2016
DOI: 10.15171/jnp.2017.02
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin attenuates chromium-induced nephrotoxicity in rats

Abstract: BackgroundHexavalent Chromium (Cr (VI)) compounds are extremely toxic and have been demonstrated to induce nephrotoxicity associated with oxidative stress in humans and animals. The wide environmental distribution of these agents lead to an increase interest of preventive effects of its adverse effects. ObjectivesThe propose of the present study was to determine the potential protective effects of simvastatin (SIMV) on Cr (VI)-induced nephrotoxicity in rat. Materials and MethodsForty-eight adult male Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Acute Cr(VI) toxic group revealed a significant increase in the level of liver malondialdehyde (MDA) as compared to the control group .Similar finding was reported by Goodarzi et al, (2016)and Hegazy et al, (2016) while Cengiz et al, (2016) observed that the level of MDA had not changed in K2Cr2O7 treated rats as compared to the control group.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Acute Cr(VI) toxic group revealed a significant increase in the level of liver malondialdehyde (MDA) as compared to the control group .Similar finding was reported by Goodarzi et al, (2016)and Hegazy et al, (2016) while Cengiz et al, (2016) observed that the level of MDA had not changed in K2Cr2O7 treated rats as compared to the control group.…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, there were significant increase in superoxide dismutase (SOD) activity and significant decrease in the serum level of reduced glutathione (GSH) and catalase activity in acute Cr(VI) toxic group as compared to the control group similar to Goodarzi et al, (2016).However, Cengiz et al, (2016) observed that SOD, catalase and reduced GSH levels had not changed in K2Cr2O7 treated rats .…”
Section: Discussionsupporting
confidence: 42%
“…Atorvastatin belongs to a class of statins with indicated antioxidant (10 mg/kg, for 10 days) (Pal et al, 2015), antithrombotic (10 mg/kg/day) (Ozbek et al, 2009), immune-modulatory (40 mg for 4 weeks) (Fuentes-Orozco et al, 2018), and antitumor effects in experimental animal models (Garjani et al, 2012). Atorvastatin at 20 mg/day decreased inflammation through HMG-CoA reductase inhibitors, lowered low-density lipoprotein (LDL) cholesterol in plasma, and promotion of antioxidant effects by suppressing oxidation pathways (Goodarzi et al, 2016; Wang et al, 2017). Atorvastatin is a reductase inhibitor and effective in altering lipid profiles, lipid peroxidation, and antioxidant systems (Yan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[76]Because heavy metals are excreted mostly through the kidneys, excess levels of hexavalent chromium [Cr (VI)] are accumulated there which causes nephrotoxicity. [77]Chromium has the ability to influence cellular functioning by blocking antioxidant enzymes and binding to antioxidant components such as Glutathione (GSH), contributing to oxidative stress. In, proximal convoluted tubules, chromium compounds are selectively deposited where they produce acute tubular necrosis in large dosages after parenteral administration.…”
Section: Chromium Induced Nephrotoxicitymentioning
confidence: 99%